Pengelolaan MGBK Dalam Meningkatkan Profesionalisme Guru Bimbingan Dan Konseling SMA/MA - Margaretha Diah Retno Sulistyowati (Media Manajemen Pendidikan, 2018)
Initially, this research was conducted to know and present the description or information about (1) MGBK program management in improving the professionalism of teachers and counseling SMA / MA Bantul Regency, as a recommendation material for the management of MGBK next period. (2) the participation of guidance and counseling teacher of SMA / MA of Bantul Regency in following MGBK activities; (3) the efforts made in increasing teacher participation in MGBK activities. However, after the research was conducted for almost a semester, not only those things in advance were found, but also information about the fulfillment of standard development of MGBK as well as fulfillment of operational standards of organization of MGBK SMA / MA Bantul Regency.The method used in this research is qualitative based on postpositivism / Interpretative philosophy. The focus of the research is the active participation of the BK Teachers in the MGBK activities in relation to the increased professionalism of BK Teachers SMA / MA Bantul District. The research data was obtained from the event during the activity process of MGBK activity, with the informants of BK Teachers, BK Board, Principals, and Subject Teachers. The techniques used in this data collection are interviews, observations and document studies, which are complemented by photographs of activities. Analysis begins from the field or empirical facts by plunging into the field, studying, analyzing, interpreting, and drawing conclusions from existing phenomena in the field.Keywords: Teacher Participation BK; MGBK, Professionalism